Salvage microbiology: opportunities and challenges in the detection of bacterial pathogens following initiation of antimicrobial treatment. (March 2015) - Farrell, John J; Hujer, Andrea M; Sampath, Rangarajan; Bonomo, Robert A
<x xml:space="preserve">Abstract</x> Broad-range 16S ribosomal RNA gene PCR coupled with Sanger sequencing was originally employed by soil scientists and was subsequently adapted for clinical applications. PCR coupled with electrospray ionization mass spectrometry has also progressed from initial applications in the detection of organisms from environmental samples into the clinical realm and has demonstrated promise in detection of pathogens in clinical specimens obtained from patients with suspected infection but negative cultures. We review studies of multiplex PCR, 16S ribosomal RNA gene PCR and sequencing and PCR coupled with electrospray ionization mass spectrometry for detection of bacteria in specimens that were obtained from patients during or after administration of antibiotic treatment, and examine the role of each for assisting in antimicrobial treatment and stewardship efforts. Following an exploration of the available data in this field, we discuss the opportunities that the preliminary investigations reveal, as well as the challenges faced with the implementation of these strategies in clinical practice.